A new idea each morning : how food and agriculture came together in one international organisation - Way, Wendy (ANU E Press, 2013)
"The creation of an international organisation bringing together the needs of the hungry and the interests of farmers seems so logical that it is hard to imagine how revolutionary it was in the first half of the twentieth century"--Intrduction